APLIKASI ANALISIS SHIFT SHARE ESTEBAN-MARQUILLAS PADA SEKTOR PERTANIAN DI KABUPATEN BOYOLALI - -, ROPINGI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
In OTDA era, data and information about allocation effect is very important, becouse its became competitive advantage in this region. The other opportunity is investor pulled with this region. This research was done in Boyolali Regency. Assessing data from BPS Central Java., Boyolali Regency The data and information used in this research was data Gross Regional Domestic Product (GRDP) from 1998 to 2002.. Type of data is secundary. For analysing this research used Esteban- Marquillas Shift Share Analysis (Dinamic SSA/ E-M SSA). The result of this research is (i) Agriculture, Financing, Ownership and Bussiness Services included sectors have competitive advantage, specialized (Code 4). (ii)Electricity, Gas, Water Supply, Contruction and Services included sectors have competitive advantage, not specialized (Code 3). (iii) Mining and Quarrying, Industies included sectors have competitive disadvantage, not specialized (Code 2) (iv) Trade, Hotel, Restaurant, Transport and Comunication included sectors have competitive disadvantage, not specialized (Code 1). (v) Agricultural sector what it has competitive advantage, specialized (Code 4) are foodstuff plants, and plantation plants. It has competitive advantage, not specialized are foresting and fishing, whereas cattle sector included sector has competitive disadvantage, not specialized (code 1) (vi) The contribution of Agricultural Sector periode 1998 to 2002 in the economy Boyolali regency if seen income multiplier, it trend rise except in 2001, it contribution decreased.
Keywords: Allocation Effect; Boyolali Regency; Esteban Marquillas SSA